Analisis Kualitas Layanan Terhadap Kepuasan Pengguna Aplikasi Clean Hris Menggunakan Metode Webqual 4.0 - Maria Fatima Jedo Tukan; Mochammad Abdul Azis; Ahmad Fauzi; Ginabila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the effect of Clean HRIS website service quality on user satisfaction using the WebQual 4.0 method. The independent variables in this study consist of usability, information quality, and service interaction quality, while the dependent variable is user satisfaction. This research applies a quantitative approach, with data collected through questionnaires distributed to 100 active users of Clean HRIS. The data were analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results show that the three WebQual 4.0 variables, namely usability, information quality, and service interaction quality, have a positive and significant effect on user satisfaction. The coefficient of determination indicates that service quality variables are able to explain a substantial proportion of the variation in user satisfaction with the Clean HRIS website. Descriptively, users are categorized as satisfied with the aspects of usability, information quality, and service interaction quality. Therefore, the service quality of the Clean HRIS website plays an important role in improving user satisfaction. This study recommends that application managers continuously improve information clarity, ease of navigation, interface design, and service responsiveness to enhance user satisfaction in a sustainable manner.